KONSERVASI EKOLOGI PESISIR: PENGOLAHAN LIMBAH TEMPURUNG KELAPA BERBASIS ECO-ART YANG BERNILAI EKONOMIS DAN ICONIC - Muhammad, Fuad; Andriani, Risa; Devara, Hafiz Rama; Abdillah , Rangga Fajar; Sari, Suzanna Ratih (Jurnal Abdi Insani, 2024)
Cocos Nucifera or coconut plays an important role in the life of Indonesian coastal communities, including in Punjulharjo Village, Rembang, Central Java, which relies on coconut as an economic resource due to the presence of tourist activity on Karang Jahe Beach. However, this activity also leads to the accumulation of coconut waste which is an urgent, challenging environmental problem in waste management. The solution to such problems can be achieved through community creativity in creating eco-art from coconut bird waste, such as plant pots and pop-up books that depict the history and culture of the village. The process of making a ship's pot involves the use of special tools such as a gerinda machine, alteco glue, wooden beams, plots, and boardmarker to form a dry fence into a useful pot. While the pop-up book process itself is done using Adobe Illustrator to illustrate the discovery of cultural elements that it has. This solution will not only reduce the accumulation of coconut waste, but will increase the economic value of Punjulharjo Village. Ships serve as a tool to convey messages about people's relations with the sea and their maritime history. In addition, the pop-up book serves as an educational tool for tourists, enhancing their understanding of local history, culture, and village characteristics. This eco-art product offers substantial economic benefits and is a meaningful attraction for visitors. The use of eco-art-based coconut poultry waste can reflect a holistic approach to environmental conservation, cultural identity, education, and economic empowerment. These sustainable initiatives highlight the potential for positive change when dealing with environmental, cultural, and economic aspects together. For example, addressing waste issues, raising incomes, and promoting local cultural heritage, as well as preserving coastal ecology.